Analisis Hubungan Jenis Kecerdasan Majemuk dengan kemampuan Kognitif Mahasiswa - Sakinah Zubair; Munawwarah (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2024)
Revealing the types of multiple intelligences possessed by students provides information about the uniqueness of each student. Therefore, this research aims to determine the relationship between students' multiple intelligence types and their cognitive abilities. Cognitive abilities in this research are limited to student learning outcomes in Student Development courses. This type of research is survey research with a type of data analysis, namely descriptive analysis. The participants in this research were 30 UNM chemistry students. The instruments used were questionnaires to determine students' multiple intelligence types and learning outcomes tests to determine students' cognitive abilities. Of all participants, five types of intelligence were obtained, namely 30% Intrapersonal, 26.67% Interpersonal, 23.22% Mathematical Logic, and 10% Naturalistic and Musical. Based on the average test scores on learning outcomes, it is known that there is no significant difference in the cognitive abilities of students in various multiple intelligence groups.